PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) MAPEL GAMBAR TEKNIK MANUFAKTUR - Dhani Aryanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
This study aims to improve student activity and learning outcomes in the subject of Manufacturing Engineering Drawing class XI TPm 3. Observation Results In this subject the teacher is still actively involved in the learning process or commonly called teacher centered. In the learning process the teacher conveys learning using an LCD projector, the teacher gives instructions or examples then students imitate what is exemplified. But in the process students have difficulty following the instructions from the teacher, the teacher must repeat the instructions until the students understand. This takes up a lot of time during the learning process. So there are other topics that the teacher cannot convey to students. Teachers feel unable to deliver teaching materials optimally because of limited teaching hours.The research method used is to apply the Project Based Learning (PjBL) learning model with the subjects of class XI TPm 3 students. Data collection techniques use evaluations in the form of LKPD in which there is an evaluation of knowledge and performance.The results of the holding of students, pre-test before learning cycle 1 obtained results of 39, only a few students who mastered the function of making and modifying 2D CAD drawings. 9 students who are quite mastered and 30 students who have not mastered. After filling out the questionnaire, it turned out that the reason was that the majority of children did not know about 2D drawing with computer applications